Social policy : an introduction - Blakemore, Kenneth. 1948- (Buckingham ; Phildelphia : Open University Press, 2003)
"Social Policy: An Introduction is essential reading for students beginning or building on their study of social policy or welfare. It can be used in undergraduate degree courses, postgraduate diplomas and Masters level and pre-degree studies. The book is an invaluable reference resource for practitioners, professionals of policy makers in fields including health, medicine and nursing, housing, social services and counselling, education, law and criminology."--BOOK JACKET.
Includes bibliographical references p. 276-284 and index.
Keywords: Social policy; Great Britain -- Social policy